1992
DOI: 10.2307/1166190
|View full text |Cite
|
Sign up to set email alerts
|

Self-Evaluation in Young Children

Abstract: A series of studies was conducted to examine the development of self-evaluation in children aged 1-5 years. Developmental changes in children's reactions to achievement-related outcomes were assessed in a variety of contexts, using different tasks and different criteria for success. The first study of 1-3-year-olds revealed an increased social orientation after the age of 21 months. Only children over this age were more likely to look up at the experimenter after they had produced an outcome themselves than af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(131 citation statements)
references
References 10 publications
3
126
1
1
Order By: Relevance
“…Western children have been found to show several components of both expressions in response to experimentally manipulated achievements or failures (18)(19)(20)(21) and examination success (22). However, studies have not coded behavioral responses to naturalistic successes and failures for all components of the prototypical pride and shame expressions or examined the issue cross-culturally.…”
mentioning
confidence: 99%
“…Western children have been found to show several components of both expressions in response to experimentally manipulated achievements or failures (18)(19)(20)(21) and examination success (22). However, studies have not coded behavioral responses to naturalistic successes and failures for all components of the prototypical pride and shame expressions or examined the issue cross-culturally.…”
mentioning
confidence: 99%
“…These expressive features are described in Table 1. The table also includes several signs drawn from the work of other investigators (Barrett et al, 1993;Lewis et al, 1992;Stipek et al, 1992), and a mediated form of expression observed in the present study (see below).…”
Section: Coding Of Shame Signsmentioning
confidence: 96%
“…Observations were made of girls' reactions to failure on easy tasks that had been modified to prevent success, using tasks and procedures developed by previous investigators to study self-evaluation in young children (Geppert, 1986;Lewis et al, 1992;Stipek et al, 1992). It has been shown that children as young as 3 years of age have negative self-evaluative reactions, including shame, when they fail tasks they appear to judge as easy and therefore within their capability (e.g.…”
Section: Observational Assessment At Timementioning
confidence: 99%
See 1 more Smart Citation
“…Pride-driven choices and pride displays occur in every known culture (33) and appear reliably and early in development (34)(35)(36). Pride is triggered by achievements (35,37), aggressive formidability (38,39), and other factors of social value such as attractiveness and membership in a powerful coalition (40).…”
Section: The Advertisement-recalibration Theory Of Pridementioning
confidence: 99%